An analysis of process fault diagnosis methods from safety perspectives. (February 2021) - Arunthavanathan, Rajeevan; Khan, Faisal; Ahmed, Salim; Imtiaz, Syed
Highlights: This paper analyzes the interconnection of fault detection and diagnosis, risk assessment and abnormal situation management. The paper reviews the existing methods and models related to fault detection and diagnosis, abnormal situation management, and risk. The paper also present authors' thoughts on the research direction in the area of process safety in industrial 4.0. This paper aims to serve as a road map for process safety research to enable safer and sustainable development. Abstract: Industry 4.0 provides substantial opportunities to ensure a safer environment through online monitoring, early detection of faults, and preventing the faults to failures transitions. Decision making is an important step in abnormal situation management. Assigning risk based on the consequences may provide additional information for abnormal situation management decisions to prevent the accident before it occurs. This paper analyzes the interconnections between the three essential aspects of process safety: fault detection and diagnosis (FDD), risk assessment (RA), and abnormal situation management (ASM) in the context of the current and next generation of process systems. The authors present their thoughts on research directions in process safety in Industry 4.0. This article aims to serve as a road map for the next generation of process safety research to enable safer and sustainable process operations and development.